2014 International Conference on Advances in Computing, Communications and Informatics (ICACCI) 2014
DOI: 10.1109/icacci.2014.6968635
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Aid for Mango cutting (AAM)

Abstract: Mango cultivation methods being adopted currently are ineffective and low productive despite consuming huge man power. Advancements in robust unmanned aerial vehicles (UAV's), high speed image processing algorithms and machine vision techniques, reinforce the possibility of transforming agricultural scenario to modernity within prevailing time and energy constraints. Present paper introduces Agricultural Aid for Mango cutting (AAM), an Agribot that could be employed for precision mango farming. It is a quadcop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…With the exception of one conference presentation [33], there is no scientific literature on automation trials for mango harvesting, as revealed by a Scopus search of the string 'mango AND robotic OR mechanical AND harvest'. However, several foundation technologies are now in place.…”
Section: Mango Harvestmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of one conference presentation [33], there is no scientific literature on automation trials for mango harvesting, as revealed by a Scopus search of the string 'mango AND robotic OR mechanical AND harvest'. However, several foundation technologies are now in place.…”
Section: Mango Harvestmentioning
confidence: 99%
“…Konam [33] presented a conceptual design of a mango harvest using a quadcopter equipped with a blade as an end effector to cut the fruit stalk, with fruit falling into nets under the tree. This concept does not seem feasible because fruit will be damaged falling through the tree canopy and hitting fruit already in the net, and exuded sap will deteriorate the quality of fruit if it is left sitting on the capture net for more than a few seconds.…”
Section: Mango Harvestmentioning
confidence: 99%
“…Therefore, most UAS equipped with grippers and other robotic attachments will be designed for specific niche purposes. A good example comes from Konam who proposed a design that would use a robotic arm to cut ripened mangos and collect them in a net located at the base of the tree, which is work that cannot be effectively done by a ground-based system given tree heights [103]. Addressing a similar situation, Varadaramanujan and his colleagues present another UAS equipped with a robotic end-effector which can be used to pick fruits and vegetables from hard to reach areas [104].…”
Section: Gripping Toolsmentioning
confidence: 99%
“…In these cases, the robots are usually expected to play an active role on the agricultural process. Among others [9] and [10] present two innovative solutions for automated harvesting, while in [11] the cutting of a specific tree is considered. In this scenario, the researchers of the Politecnico di Torino developed a novel wheeled UGV tailored on precision agriculture tasks and specifically design for monitoring and sampling of crops and soil [12][13][14].…”
Section: Introductionmentioning
confidence: 99%